Expression Of Recombinant Human Dna Topoisomerase In Pichia Pastoris And Analysis Of Its Activity - Chan, Mooi Kwai (2017)
This study was aimed to establish a method to produce in-house recombinant human DNA topoisomerase. The DNA topoisomerase I (Topo I) and DNA topoisomerase II (Topo II) coding regions were amplified from the cDNA of breast cancer cells, MDA-MB-231. Topo I and Topo II coding region were ligated into expression vector, pPICZ--A and pPICZ--C, respectively. Subsequently, the constructed recombinant vectors were transformed into four types of Pichia pastoris strain, X-33, GS115, SMD1168H and KM71H. PCR screening for recombinant clones was performed and followed by selection of multicopy clones using agar plates containing increasing concentrations of Zeocin. The selected multicopy clones were then induced for enzymes expression in a shake flask system. Topo I was expressed relatively higher in GS115 than other Pichia strains.